The Oxford handbook of theology, sexuality, and gender - Thatcher, Adrian (Oxford University Press, 2017)
The Oxford handbook of theology, sexuality, and gender presents an unrivalled overview of the theological study of sexuality and gender. Not merely contentious and pervasive topics, sexuality and gender have escalated in importance within theology. Theologians increasingly agree that even the very doctrine of God cannot be contemplated without a prior grappling with each. Featuring 41 newly-commissioned essays, written by the foremost scholars in the discipline, this authoritative collection presents and develops the latest thinking in the area. Divided into eight thematic sections, the Handbook explores key methodological approaches, concepts, and issues, as well as current controversies within various denominations. Selected essays draw on reason as a distinct source of theology, discussing evolutionary biology and behavioural genetics, psychology, anthropological research, philosophical research, and queer theory. It examines the history of theologies of sexuality and gender, with close analysis of the Bible and the Christian tradition. The final section considers theology in relation to different expressions of sexual identities. This volume is an essential reference for students and scholars, which will also stimulate further research